Sistem Informasi Manajemen untuk Pengelolaan Data Administrasi Kesiswaan di MA Ihyaul Ulum Dukun Gresik - Akidatul Izza; Pusvyta Sari (Mudir : Jurnal Manajemen Pendidikan, 2019)
The aims of this study or journal is to describe the information management system at MA Ihya ul Ulum Dukun Gresik, Indonesia in managing student administration data. Research data collected by participatory observation, in-depth interviews and documentation studies. The results of this study indicate that MA Ihyaul Ulum Dukun Gresik, Indonesia uses an open management information system ERD (Entity Reality Diagram) model. This model is in the form of making information processing diagrams, storing and using them so that they are ready to be accessed according to their needs. The implementation of this system is supported by internet connection, hardware and software that are well maintained. This system has flow of information that can be understood very easily. The information management system is consistent and sustainable. The system need optimal supervision by headmaster and stakeholder, regular maintenance, and awareness and skills of all users to care and use all equipment properly.